Song of Transformation: Performing Iroquoian Identity Through Non-Traditional Song - Valentine, Lisa (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2003)
AbstractFirst Nations Englishes display continuity in discourse structuring, even when the speaker is monolingual in English. This article documents this cultural and discursive continuity through the analysis of a young Seneca songwriter’s performance of an original non-traditional song, written and sung in English. The analysis highlights key features of traditional Iroquoian discourse as they appear in the song text, and ties those discursive strategies to the social and political context of the performance venue, the songwriter’s family and the Six Nations community. This multilevel ethnomusicological analysis explores issues of genre and style as they relate to identity and resistance in the context of a Canadian First Nation.